Scanning acoustic tunneling microscopy and spectroscopy: A probing tool for acoustic surface oscillations - Hesjedal, T; Chilla, E; Frohlich, H (1997)
A method is presented for the universal probing of surface acoustic waves (SAWs). For measuring high frequency SAWs by scanning tunneling microscopy (STM) a stroboscopic snapshot technique was employed, named scanning acoustic tunneling microscopy. The amplitude and the phase of a state of oscillation within a SAW field are a superposition of the surface topography and the oscillation trajectory. Measuring with atomic resolution the observed contrast can be understood by a spherical tunneling model. A STM based system is proposed that reaches submicron resolution for the quantitative evaluation of elastic constants. With this system the velocity dispersion is obtained from the detection of laser generated SAW pulses by a broadband STM. Scanning acoustic tunneling spectroscopy using different acoustic modes opens a door for quantitative studies of nanoscale structures. © 1997 American Vacuum Society.